2003
DOI: 10.1007/s00422-003-0419-5
|View full text |Cite
|
Sign up to set email alerts
|

Muscle synergies during shifts of the center of pressure by standing persons: identification of muscle modes

Abstract: When a standing person performs a movement such that the center of gravity shifts, the activity of postural muscles adjusts to keep the balance. We assume that such adjustments are controlled using a small set of central variables, while each variable induces changes in the activity of a subgroup of postural muscles. The purpose of this study has been to identify such muscle groups (muscle modes or M-modes) and compare them across tasks and subjects. Four tasks required the subjects to release a load from exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
160
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 174 publications
(178 citation statements)
references
References 26 publications
13
160
0
5
Order By: Relevance
“…The ΔIEMG N indices for each subject were subjected to PCA. Consistent with previous studies (Krishnamoorthy et al, 2003a, Wang et al 2005, across all subjects for three test sessions, we found that the first three PCs (PC 1 , PC 2 and PC 3 ) had at least one muscle index significantly loaded. Principal components from PC 4 onward explained little variance in the ΔIEMG N space and were poorly reproducible across subjects.…”
Section: Pca Of the Data Obtained In The Vs And Lr Taskssupporting
confidence: 92%
See 4 more Smart Citations
“…The ΔIEMG N indices for each subject were subjected to PCA. Consistent with previous studies (Krishnamoorthy et al, 2003a, Wang et al 2005, across all subjects for three test sessions, we found that the first three PCs (PC 1 , PC 2 and PC 3 ) had at least one muscle index significantly loaded. Principal components from PC 4 onward explained little variance in the ΔIEMG N space and were poorly reproducible across subjects.…”
Section: Pca Of the Data Obtained In The Vs And Lr Taskssupporting
confidence: 92%
“…The voluntary sway task was impossible to be performed while standing on the unstable board. Hence, we used a load release (LR) task, as in a number of earlier studies (Krishnamoorthy et al 2003a(Krishnamoorthy et al , b, 2004. Note that the composition of the modes was similar across all the cited studies and methods of their identification.…”
Section: General Designmentioning
confidence: 99%
See 3 more Smart Citations